The effects of government subsidies on new energy vehicle enterprises: The moderating role of intelligent transformation. (June 2020) - Yu, Feifei; Wang, Liting; Li, Xiaotong
Abstract: In this study, subsidies are classified into government subsidies beforehand (GSB) and government subsidies afterwards (GSA). We examine the impacts of GSB and GSA on the financial performance of Chinese enterprises of New Energy Vehicle (NEV). Analyzing a dataset of Chinese NEV firms' financial performance from 2013 to 2017 with panel regression models, we demonstrate that the two forms of government subsidies have different impacts on New Energy Vehicle enterprises' performance. Specifically, we find a positive U-shaped relationship between GSB and financial performance and an inverted one between GSA and financial performance. We further investigate the moderating role of intelligent transformation in the relationships between government subsidies and NEV enterprises' performance. Our empirical analysis suggests that intelligent transformation can improve the efficiency of GSA and weaken the negative effects of excessive GSA. These results highlight the importance of intelligent transformation for NEV enterprises, providing policy makers with new insights into NEV subsidy policies. Highlights: Two forms of government subsidies have different impacts on New Energy Vehicle enterprises. A U-shaped relation between government subsidies beforehand and financial performance. Intelligent transformation moderates the relationship between government subsidies afterwards and financial performance.